Different Methods to Assess the Nutritional Status of Alzheimer Patients. (2nd January 2021) - Martínez-Tomé, Magdalena; Murcia, M Antonia; Rosario, Claudia; Mariscal-Arcas, Miguel; Jiménez-Monreal, Antonia M
Abstract: Objective: To assess the body composition and nutritional state of patients with Alzheimer's (Global Deterioration Scale GDS-4) using different methods and to investigate the correlation among methods. Methods: A total of 25 Alzheimer GDS-4 patients participated in this transversal descriptive observational study, which used anthropometry, Mini Nutritional Assessment (MNA), the Nutrition Screening Initiative Check List (NSI) and a 24-hour recall questionnaire (R24h). Results: Anthropometric observations pointed to obesity in patients of both sexes. The MNA showed that 76% of the population was "at risk of malnutrition", and the NSI suggested that 32% had a high nutritional risk, 48% had an "average" nutritional risk, and the remaining 20% a low nutritional risk. The Bland-Alman concordance plot between the NSI and MNA tests pointed to a high degree of agreement, meaning that both tests provided similar results for the group of studied subjects. The nutritional analysis, based on the Kruskal-Wallis test, showed there were significant differences between R24h and MNA in the case of ascorbic acid, iron, zinc and potassium (p < 0.05), and between R24h and NSI in the case of the double unsaturation index and vitamin D3 (p < 0.05). These results suggest that both questionnaires are equally valid for evaluating the nutritional status of Alzheimer patients. Conclusion: Although the NSI and MNA tests provide similar results, we recommend an initial nutritional assessment using the NSI since it is short but provides information on any alteration in food intake as a result of restrictions and/or metabolic alterations.